Parental Self-Efficacy in Foresting Independence in Children with Down Syndrome: A Case Study on Individuals with Down Syndrome - Anggit Rahayu; Umi Nur Kholifah; Resy Vahmi (PROMOTOR, 2023)
The formation of independence for children with Down syndrome can be implemented using democratic parenting patterns carried out by parents for children with special needs, democratic parenting patterns are strict and independent parenting patterns with no opportunities for children to determine their desires, it can be said that democratic parenting patterns are the process of giving punishment and reward given by parents to their children. Parents' self-efficacy plays an important role in the process of independence for children with Down syndrome in overcoming abnormalities in their children due to abnormalities in chromosome 21/trisomy, namely abnormalities that occur in the indicated child's cell metabolism system. The purpose of this article is to describe the self-efficacy of parents in fostering the independence of children with Down syndrome (case studies on individuals with Down syndrome). This study uses a descriptive qualitative method based on case studies. The results of the study show that parents' self-efficacy in fostering the independence of children with Down syndrome is closely related to the child's independence process. Seen in democratic parenting patterns, parents provide rewards if the child can work according to the instructions given. On the other hand, the child will be given punishment when he fails to adjust the orders given. So, parents' self-efficacy in fostering children's independence with a democratic parenting pattern is one of the tips for implementing children's independence through actions and challenges given to children so that children can hone their soft skills and hard skills.